The Development of Electrocardiogram Recorder as a Portable Internet Appliance - Ng, Kwan Ti (2001)
Electrocardiogram (EGG) has long been used as an important medical tool in monitoring patient's heart activities. In some cases, the patient has to go to the medical center very often to record their EGG for the diagnostic of the physician. This thesis describes the design and development of an electrocardiogram (EGG) recorder for single-lead recording that enables the recording of EGG at home and development of software to receive the EGG data from the recorder. The EGG data is saved in a compressed format for easy transmission over the Internet. The EGG recorder is a battery-powered device and its design emphasises on low power consumption. The EGG recorder is used as a peripheral connected to the computer via RS-232 port. The software was developed by using Visual G++ programming language. At the end of the project, an EGG recorder has been constructed and its characteristics have been tested. The software can display the EGG data and clearly show the P, Q, R, S and T waves for diagnosis.